Sekuritisasi Kabut Asap di Singapura, 1997-2014 - Kardina Gultom (Universitas Diponegoro, 2016)
Transboundary haze pollution is one of environmental problems in ASEAN that had caused serious impact toward some countries in the region, include Singapore. Due to the failure of Indonesian government in controlling the forest and land conflagration, Singapore conducted securitization against haze issue. This research aims to explain haze securitization concluded by Singapore government in 1997-2014. This research employs’s Barry Buzan theory on securitization. This research pound that haze securitization was successfully conducted by Singapore goverment with variety of efforts, such as sending memorandum to Indonesian government, ratification of ASEAN Agreement on Transboundary Haze Pollution (AATHP), bilateral cooperation to overcome the haze problem and announcing the Transboundary Haze Pollution Act. However, the securitization did not influence Indonesia and Singapore bilateral relations.Keywords: transboundary haze pollution, Indonesia, securitization, Singapore